Neuere Entwicklungen auf dem Gebiet der Chemie organischer Pigmentfarbstoffe - F. Kehrer (CHIMIA)
The patent literature for the period 1960-1972 is surveyed and areas of structural emphasis in organic pigment research are summarized. Representative syntheses of quinacridone, metalcomplex and anthraquinone pigments, and newer chro- mophoric systems with pigment character are discussed in detail. The industrial consequences of these new developments are noted and the expected future directions of organic pigment research are outlined.